Implicit Measures of Suicide Risk in a Military Sample. (July 2018) - Chiurliza, Bruno; Hagan, Christopher R.; Rogers, Megan L.; Podlogar, Matthew C.; Hom, Melanie A.; Stanley, Ian H.; Joiner, Thomas E.
Suicide has become an issue of great concern within the U.S. military in recent years, with recent reports indicating that suicide has surpassed combat related deaths as the leading cause of death. One concern regarding suicide risk in the military is that existing self-report measures allow service members to conceal or misrepresent current suicidal ideation or suicide plans and preparations. Implicit association tests (IATs) are computer-based, reaction time measures that have been shown to be resilient to such masking of symptoms. The death/suicide implicit association test (d/s-IAT) is an empirically supported IAT that is specific to death and suicide. The present study examined whether the performance of 1, 548 U.S. military service members on the d/s-IAT significantly predicted lifetime suicidal ideation and depression. Zero-inflated negative binomial regression analyses were used to test these associations. Results indicated that the d/s-IAT was neither associated with history of suicidal ideation nor history of depression.